2, 2′, 4, 4′-tetrabromodiphenyl ether induces germ cell apoptosis through oxidative stress by a MAPK-mediated p53-independent pathway. (November 2018) - You, Xinyue; Xi, Jing; Liu, Weiying; Cao, Yiyi; Tang, Weifeng; Zhang, Xinyu; Yu, Yingxin; Luan, Yang
Abstract: 2, 2′, 4, 4′-Tetrabromodiphenyl ether (BDE-47), a representative congener of polybrominated diphenyl ethers in the environment, is known to have reproductive toxicity. However, the underlying mechanisms remain to be clarified, especially in in vivo systems. In the present study, we employed Caenorhabditis elegans to study the effects of BDE-47 on reproduction. Our results showed that BDE-47 impaired worm fecundity and induced germ cell apoptosis. To elucidate the mechanisms, DNA damage and oxidative stress induction were investigated by determining the numbers of foci formation in transgenic worms expressing HUS-1::GFP and the levels of reactive oxygen species, respectively. We found that BDE-47 induced oxidative stress but not DNA damage, and treatment with the antioxidant, N -acetyl-L-cysteine, completely abrogated BDE-47-induced germ cell apoptosis. In addition, the apoptosis was blocked in mutants carrying mek-1, sek-1 or abl-1 loss-of-function alleles, but not in the p53/ cep-1 deficient worms, suggesting that the mitogen-activated protein kinase (MAPK) signaling cascade was essential for BDE-47-induced germ cell apoptosis and p53/ cep-1 was not required. Moreover, the apoptosis in the strains deficient for DNA damage response was not suppressed under BDE-47 treatment. Overall, we demonstrated that BDE-47 could induce oxidative stress and subsequent germ cell apoptosis in Caenorhabditis elegans through a MAPK-mediated p53-independent pathway. Graphical abstract: Image 1 Highlights: 2, 2′, 4, 4′-Tetrabromodiphenyl ether induces germ cell apoptosis in Caenorhabditis elegans . 2, 2′, 4, 4′-Tetrabromodiphenyl ether cannot cause DNA double strand breaks in the germ cells. 2, 2′, 4, 4′-Tetrabromodiphenyl ether may induce germ cell apoptosis through oxidative stress. A p53-independent MAPK pathway is involved in 2, 2′, 4, 4′-tetrabromodiphenyl ether-induced germ cell apoptosis. Abstract : We demonstrated that BDE-47 could induce germ cell apoptosis in Caenorhabditis elegans by induction of oxidative stress through a MAPK-mediated p53-independent pathway.